2020
DOI: 10.3390/nu12092712
|View full text |Cite
|
Sign up to set email alerts
|

A Humanities-Based Explanation for the Effects of Emotional Eating and Perceived Stress on Food Choice Motives during the COVID-19 Pandemic

Abstract: Perceived stress affects emotional eating and food choices. However, the extent to which stress associates with food choice motives is not completely understood. This study assessed whether emotional eating mediates the associations between perceived stress levels and food choice motives (i.e., health, mood, convenience, natural content, price, sensory appeal, familiarities, weight control, and ethical concerns) during the Coronavirus Disease 2019 pandemic. A total of 800 respondents were surveyed in the Unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
75
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 112 publications
6
75
0
14
Order By: Relevance
“…An individual may use food to cope with their internal emotions, as well as with external stressors, such as change of employment status [ 28 ]. Our findings are consistent with numerous studies from Europe [ 7 , 34 , 35 , 36 ] and North America [ 3 , 6 , 64 ] indicating that during the COVID-19 outbreak increased feelings of depression, anxiety, and stress, and a worsened mental state was associated with emotional eating. Indeed, COVID-19 appeared to have a clear relationship to eating behaviors, particularly eating more snack-type foods [ 3 , 11 ].…”
Section: Discussionsupporting
confidence: 93%
“…An individual may use food to cope with their internal emotions, as well as with external stressors, such as change of employment status [ 28 ]. Our findings are consistent with numerous studies from Europe [ 7 , 34 , 35 , 36 ] and North America [ 3 , 6 , 64 ] indicating that during the COVID-19 outbreak increased feelings of depression, anxiety, and stress, and a worsened mental state was associated with emotional eating. Indeed, COVID-19 appeared to have a clear relationship to eating behaviors, particularly eating more snack-type foods [ 3 , 11 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the COVID-19 pandemic may be associated with other problems related to the general interruption of routines and social interactions, which influence not only mental health [ 46 ], but also dietary behaviors and emotional eating [ 47 , 48 ]. Similarly, panic-buying or stockpiling of long-life foods, such as flour, sugar, dried pasta, rice, biscuits, and bottled and canned foods, may also contribute to increased consumption and overeating [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was also demonstrated in another Italian study, which found half of their sample felt they had modified their dietary habits during the lockdown, with 42% attributing an increase in food intake to higher anxiety levels ( Scarmozzino & Visioli, 2020 ). An American study reported that perceived stress was significantly correlated with emotional eating during the pandemic, and that self-reported emotional eating mediated identified associations between perceived stress and food choice motives of mood, convenience, sensory appeal, price and familiarity ( Shen, Long, Shih, & Ludy, 2020 ). It also discussed the role of comfort food during previous crises, with eating playing a significant role in alleviating stress and improving mood (see Shen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…An American study reported that perceived stress was significantly correlated with emotional eating during the pandemic, and that self-reported emotional eating mediated identified associations between perceived stress and food choice motives of mood, convenience, sensory appeal, price and familiarity ( Shen, Long, Shih, & Ludy, 2020 ). It also discussed the role of comfort food during previous crises, with eating playing a significant role in alleviating stress and improving mood (see Shen et al, 2020 ). Situational explanations for increased emotional eating during this time may also include the fact that it is found to be more frequent when individuals are alone and eating at home ( Baumeister, Heatherton, & Tice, 1994 ).…”
Section: Introductionmentioning
confidence: 99%